Jane Austen and representations of Regency England - Sales, Roger (Routledge, 1996)
This book firmly asserts Austen as a regency writer concerned about material social history issues. It illustrates how Austen's later work, including her letters, represent major historical developments of her period far more openly and directly than is generally recognised. It also depicts the ways in which the Austen novels represent dandyism and masculine identities, the Regency crisis and condition-of-England themes such as healthcare and national identity. -- Publisher description.